2(
x + 4) =
x + 4 which is the second option is the equivalent expression.
Explanation:
First, we need to calculate the value of two-fifths of x. It means 2 portions out of the five portions of x which equates to
x.
Now we calculate the values of the two expresssions on the LHS.
1) 2 (two-fifths x + 2) = 2 (
x + 2) =
x + 4.
2) (two-fifths x + 4) = 2(
x + 4) =
x + 8.
Now we determine values of the four expressions on the RHS.
1) Two and two-fifths x + 1 = 2
x + 1
2) Four-fifths x + 4 =
x + 4
3) Four-fifths x + 2 =
x + 2
4) Two and two-fifths x + 8 = 2
x + 8.
Out of the various LHS and RHS values, the
LHS value and
RHS value is the same. So option 2 is the answer.
Hi,
When x=3 and y=-3, the expression -8y+x6 becomes -8(-3) + (3)6 = 24 + 18 = 42
Hope this helps! If you’d like further explanation please let me know.
Answer:
y < -7
Step-by-step explanation:
You balance it like a normal equation:
8y + 3 > 15y + 52
8y + 3 (-8y) > 15y + 52 (-8y)
3 (-52) > 7y + 52 (-52)
-49 (÷7) > 7y (÷7)
y < -7
The answer is b for your answer
But we can put it that way